A representação social de Dilma Rousseff: uma análise das charges que a retratam na Folha de S. Paulo - Ferraz, Gabriel Pinelli (2013)
This research aims to analyze the construction of the social representation of Dilma Rousseff from the cartoons that depict her in the Folha de S. Paulo. The cartoon has an important history in dealing with political affairs. Through satire and humor, it promotes synthesis of the political themes of his time, while opines and makes critical. As a media vehicle built by via of the ridicule, the cartoon can take the reader to reflect on the problems of their society. Its raw material are the issues of everyday life, it reflects on them and opines. Thus, the cartoon is characterized as opinionated journalistic genre. This research analyzed the cartoons published between January 2010 and December 2012. This period included the election process and the first half of the Dilma government. Were collected for analysis 171 cartoons. The set of selected cartoons was analyzed using Content Analysis. The cartoons construct the social representation of Dilma by comparing her to political allies and her opponents, linking her to Lula and assigning meanings to her government. From this, Dilma was represented as product of Lula, as unable political negotiator, as a fighter of corruption and as a manager public incompetent